Planktonic foraminifera and calcareous nannofossils record in the upper Campanian-Maastrichtian pelagic deposits of the Malatya Basin in the Hekimhan area (NW Malatya, eastern Anatolia) - Korkmaz, Taner; Petrizzo, Maria Rose; SARI, BİLAL; YILDIZ, AYŞEGÜL (Cretaceous Research, 2016)
The uppermost Cretaceous (upper Campanian-Maastrichtian) pelagic successions from the Malatya Basin (NW Malatya, eastern Anatolia) were studied by 688 samples, which were collected from five strati graphic sections in the Hekimhan area. The pelagic deposits conformably overlie rudist bearing shallow water limestones and are overlain conformably by Maastrichtian dolomites and unconformably by Paleocene-Eocene deposits, respectively.